PENGARUH ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL DISCLOSURES DAN ASSURANCE SUSTAINABILITY REPORT TERHADAP FIRM VALUE - Vina Aprillia (2021)
This study aims to examine the effect of environmental performance, environmental disclosures and assurance sustainability report on firm value. This study also uses firm size, leverage and sales growth as control variables. Firm value as dependent variable is proxied by Tobins'sQ. Environmental performance as an independent variable is proxied by the PROPER rating from the Ministry of Environment and Forestry Republic of Indonesia (KLHK). Environmental disclosures use an index from the GRI G4 or GRI Standards. Assurance Sustainability Report is proxied by a dummy variable which is given 1 if there is assurance in sustainability report and 0 if there isn't assurance in sustainability report. The sample in this study amounted to 72 samples from 24 non-financial companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The analysis technique used is panel data regression analysis using STATA 14.2. The results of this study indicate that environmental performance, environmental disclosures and assurance sustainability reports have no significant effect on firm value